2016
DOI: 10.1021/acs.jpcb.6b07609
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Photosynthetic Reaction Center Exhibiting Acid-Responsive Regulation of Photoinduced Charge Separation

Abstract: Nonphotochemical quenching (NPQ) is a photoprotective regulatory mechanism employed by many photosynthetic organisms to dynamically modulate energy flow within the photosynthetic apparatus in response to fluctuating light conditions. Activated by decreases in lumen pH produced during periods of high photon flux, NPQ induces rapid thermal dissipation of excess excitation energy. As a result, the rate of charge separation (CS) decreases, thereby limiting the accumulation of potentially deleterious reactive inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The photoinduced electron‐transfer properties of chromophore–acceptor and donor–chromophore–acceptor molecular assemblies have attracted substantial interest as the basis for potential applications in organic photovoltaic and dye‐sensitized solar cells . Initial formation of long‐lived charge‐separated states is one of many important aspects in the design of efficient light‐harvesting assemblies .…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…The photoinduced electron‐transfer properties of chromophore–acceptor and donor–chromophore–acceptor molecular assemblies have attracted substantial interest as the basis for potential applications in organic photovoltaic and dye‐sensitized solar cells . Initial formation of long‐lived charge‐separated states is one of many important aspects in the design of efficient light‐harvesting assemblies .…”
Section: Introductionsupporting
confidence: 63%
“…[1][2][3][4][5] Initialf ormation of long-lived charge-sepa-rated states is one of many importanta spects in the design of efficient light-harvesting assemblies. [1][2][3][4][5] Initialf ormation of long-lived charge-sepa-rated states is one of many importanta spects in the design of efficient light-harvesting assemblies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Design of new chromophores that are capable of harvesting sunlight in the low-energy visible and near-infrared (NIR) spectral envelopes attracted a lot of attention in recent decades because of the potential use of such systems in organic- and dye-sensitized solar cells. In addition, the ability to facilitate relatively strong noncovalent interactions between such chromophores and nanocarbon-based electron-accepting materials (fullerenes, nanotubes, and graphene) is thought to be advantageous in the processing of high-efficiency organic bulk heterojunction solar cells. To achieve this goal, many porphyrins, subphthalocyanines, and boron-dipyrromethenes (BODIPYs) were functionalized with a variety of electron-donating groups that improve donor–acceptor (D–A) interactions between extended π-systems. Alternatively, the introduction of the polyaromatic fragments that are either conjugated or not conjugated into chromophores’ π-system can also improve noncovalent interactions in these D–A assemblies. Covalently bound pyrene was shown to facilitate noncovalent interactions with carbon nanotubes and graphene. It has also been shown that when pyrene fragments are decoupled from the chromophores’ π-system, this extended aromatic group can facilitate an unwanted pyrene-to-chromophore electron-transfer process as well as the formation of a chromophore-centered triplet state. We have recently demonstrat...…”
Section: Introductionmentioning
confidence: 99%
“…Transient absorption (TA) spectroscopy is a broadly used technique for characterizing excited-state dynamics in a large variety of chemical systems. A small sampling of applications include understanding charge carrier transport in photosynthetic complexes, , exciton multiplication processes in small organic molecules, , and optical gain in semiconductor nanomaterials. Analyzing TA data often involves performing some kind of fitting routine that can vary in complexity depending on the characteristics of the spectra and information desired. In the simplest case, with a single or few well-separated spectral features, the data at selected wavelength points can be fit to one or more exponential decay models.…”
Section: Introductionmentioning
confidence: 99%